2010
DOI: 10.1007/s10649-010-9268-z
|View full text |Cite
|
Sign up to set email alerts
|

The significance of mathematical knowledge in teaching elementary methods courses: perspectives of mathematics teacher educators

Abstract: Our study investigates perspectives of mathematics teacher educators related to the usage of their mathematical knowledge in teaching "Methods of Teaching Elementary Mathematics" courses. Five mathematics teacher educators, all with experience in teaching methods courses for prospective elementary school teachers, participated in this study. In a clinical interview setting, the participants described where and how, in their teaching of elementary methods courses, they had an opportunity to use their advanced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
(8 reference statements)
0
8
1
Order By: Relevance
“…J. Dougherty, Bryant, Bryant, Darrough, & Pfannenstiel, 2015;Sangwin & Jones, 2017;Simon, Kara, et al, 2016;Vilkomir & O'Donoghue, 2009). Likewise, with investigations about inverse functions, most focus more on errors made by students in solving problems (Carlson et al, 2015;Kontorovich, 2017;Paoletti et al, 2018;Zazkis & Kontorovich, 2016;Zazkis & Zazkis, 2011). In this section, the researchers conclude reversible reasoning during the process of solving inverse function problems.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…J. Dougherty, Bryant, Bryant, Darrough, & Pfannenstiel, 2015;Sangwin & Jones, 2017;Simon, Kara, et al, 2016;Vilkomir & O'Donoghue, 2009). Likewise, with investigations about inverse functions, most focus more on errors made by students in solving problems (Carlson et al, 2015;Kontorovich, 2017;Paoletti et al, 2018;Zazkis & Kontorovich, 2016;Zazkis & Zazkis, 2011). In this section, the researchers conclude reversible reasoning during the process of solving inverse function problems.…”
Section: Discussionmentioning
confidence: 97%
“…It is in accordance to the findings of the previous study ( Paoletti et al, 2018;Wasserman, 2017), which suggested that researchers need to survey to assess teachers' mathematical knowledge in interpreting inverse functions. So the factors that cause students to experience confusion in the rank -1 (Kontorovich, 2017;Zazkis & Kontorovich, 2016;Zazkis & Zazkis, 2011) and students interpret functions and inverses analytically and graphically (Carlson et al, 2015) can be described in detail.…”
Section: Implication Of Reversible Reasoning For Education Learning Processmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, descriptions of K4T often highlight topics related to the current state of affairs in the field of education, such as contemporary advances in educational technologies, ethical challenges, student engagement, and unsolved problems. Researchers appear to agree that subjectspecific K4T is paramount for effective teaching and this pertains to teaching all subjects, including elementary or secondary mathematics (e.g., Zazkis & Zazkis, 2011) and science (Campbell et al, 2014;Depaepe et al, 2013).…”
Section: Knowledge For Teaching (K4t)mentioning
confidence: 99%
“…In teacher education, the relations between mathematical knowledge and pedagogical knowledge are explored and discussed extensively (e.g.,Jaworski, Wood & Dawson, 1999;Zazkis & Zazkis, 2011).…”
mentioning
confidence: 99%